On The Question of Studying Phraseological Units with Adjectives in the Classroom in Russian - Bin, Zhang (2021)
The study of phraseological units by foreign students at the stage of their professional education is an important means of enriching students ' speech, mastering the lexical norms of the Russian language. As you know, phraseological units can contain different parts of speech, but phraseological units with adjectives have the greatest expressiveness. This research is devoted to the linguodidactic problem of developing tasks for the use of phraseological units in the speech of foreign students. To successfully achieve the research goal, we used the continuous sampling method, the analysis method, the exercise method, and the observation method. Our task was to select phraseological units with adjectives and ask Chinese students to complete tasks. Some students do not know the meaning of phraseological units and the terms of their use. At the level of professional linguistic education, students should have a good command of this material. Unfortunately, due to the complexity of the material, the form of expression, and the specifics of historical and cultural features reflected in phraseology, many students were unable to correctly determine the meaning and conditions for using the proposed phraseology. We developed a system of exercises that helped students master phraseological units with adjectives, taking into account their functioning in artistic and colloquial speech. The results of our research are of interest to teachers of Russian as a foreign language and can be used in the practice of teaching foreign languages.